The trespasser eaudiobook - French, Tana (Dublin Murder Squad, 2016)
The New York Times bestselling novel by Tana French, author of the forthcoming novel The Hunter , is “required reading for anyone who appreciates tough, unflinching intelligence and ingenious plotting” ( The New York Times ). She “inspires cultic devotion in readers” ( The New Yorker ) and is “the most important crime novelist to emerge in the past 10 years” ( The Washington Post ). “Atmospheric and unputdownable.” — People  In bestselling author Tana French’s newest “tour de force” ( The New York Times ), being on the Murder Squad is nothing like Detective Antoinette Conway dreamed it would be. Her partner, Stephen Moran, is the only person who seems glad she’s there. The rest of her working life is a stream of thankless cases, vicious pranks, and harassment. Antoinette is savagely tough, but she’s getting close to the breaking point.    Their new case looks like yet another by-the-numbers lovers’ quarrel gone bad. Aislinn Murray is blond, pretty, groomed-to-a-shine, and dead in her catalog-perfect living room, next to a table set for a romantic dinner. There’s nothing unusual about her—except that Antoinette’s seen her somewhere before.   And that her death won’t stay in its neat by-numbers box. Other detectives are trying to push Antoinette and Steve into arresting Aislinn’s boyfriend, fast. There’s a shadowy figure at the end of Antoinetteʼs road. Aislinnʼs friend is hinting that she knew Aislinn was in danger. And everything they find out about Aislinn takes her further from the glossy, passive doll she seemed to be.   Antoinette knows the harassment has turned her paranoid, but she can’t tell just how far gone she is. Is this case another step in the campaign to force her off the squad, or are there darker currents flowing beneath its polished surface?